Genetic Diversity and Aggressiveness of Bipolaris oryzae in North-Central Thailand - Chaijuckam, Patcharavipa; Songkumarn, Pattavipha; Guerrero, Jonathan Jaime G. (Applied Science and Engineering Progress, 2019)
One hundred and ten isolates of Bipolaris oryzae, the causal agent of rice brown spot disease were collected from paddy fields in four provinces of north-central Thailand, including Ang Thong, Chai Nat, Lop Buri, and Sing Buri. DNA polymorphism of some Bipolaris oryzae isolates was determined by VNTR, ISSR and RAPD markers. Only VNTR-MR primer showed different fingerprint patterns among these isolates, therefore this primer was selected to study genetic diversity of the Bipolaris oryzae population. In total, there were three haplotypes corresponding to the results from cluster analysis; each of the three clusters shared identical haplotype. The majority of the isolates were separated into group A (88.18%), indicating predominant asexual reproduction of clonal population. However, there was no relationship between haplotype and either collection provinces or aggressiveness on rice. Among four rice varieties tested, including Khao Dawk Mali 105 (KDML 105), RD31, Pathum Thani 1, and Jao Hom Nin (JHN), JHN was the most resistant variety, while KDML 105 was the most susceptible to brown spot disease.